Pengaruh Kepemimpinan Kepala Sekolah, Budaya Organisasi, Dan Penguasaan Teknologi Informasi Terhadap Kompetensi Profesional Guru SD Di Kecamatan Bogorejo Kabupaten Blora - Mulyono, Pri; Kusumaningsih, Widya; Soedjono, Soedjono (PGRI Kota Semarang, 2024)
The background to this research is the reality that shows the low professional competence of elementary school teachers in Bogorejo District, Blora Regency. The principal's leadership, organizational culture, and mastery of information technology are factors that influence the low professional competence of teachers. The aim of this research is to determine the magnitude of the influence of school principal leadership, organizational culture, and mastery of information technology on the professional competence of elementary school teachers in Bogorejo District, Blora Regency. This research uses a quantitative research approach and an ex post facto type of research. The research population was all elementary school teachers in Bogorejo District, Blora Regency, totaling 158 teachers. The total research sample was 113 teachers. The analysis of this research includes normality test analysis, linearity test, homogeneity test, and multicollinearity test. Hypothesis testing includes simple regression tests and multiple regression tests. The research results show that: (1) there is a significant influence of school principal leadership on teacher professional competence of 52.0% and the regression equation formed is Y = 36.044 + 0.513X1; (2) there is a significant influence of organizational culture on teacher professional competence of 42.7% and the regression equation formed is Y = 41.257 + 0.467X2; (3) there is a significant influence of mastery of information technology on teacher professional competence of 58.0% and the regression equation formed is Y = 32.906 + 0.698X3; (4) there is a significant influence of principal leadership, organizational culture, and mastery of information technology on teacher professional competence of 62.3% and the regression equation formed is Y = 24.877 + 0.246X1 + 0.005X2 + 0.456X3.